An assessment of CO2 and CH4 emissions in a tropical river: from the Kenyir Reservoir to the estuary - Lee, Daryl Jia Jun; Mohd Ludin, Siti Farhain; Wong, Wei Wen; Zhan, Liyang; Poh, Seng Chee (PeerJ, 2025)
This study investigates the spatial and seasonal variations in CO2 and CH4 emissions from the Kenyir hydropower reservoir and its downstream Terengganu River system in Malaysia. Understanding these variations is crucial for assessing whether the greenhouse gas (GHG) budget for this aquatic continuum significantly contributes to global emissions. Malaysia’s distinct monsoonal climate presents a unique opportunity to explore the influence of seasonal hydrological changes on GHG emission dynamics in inland waters. Five sampling campaigns were performed at the reservoir to investigate this, involving three longitudinal surveys from the reservoir downstream along the Terengganu River, and two time-series samplings at the estuary between November 2017 and August 2019. Our findings reveal that GHG emissions from the Kenyir Reservoir are notably higher during the wet season (97 mmol CO2 m−2 d−1 and 2 mmol CH4 m−2 d−1) than during the dry season (54 mmol CO2 m−2 d−1 and 0.8 mmol CH4 m−2 d−1). This increase coincides with increased wind speed and potential surface mixing during the wet season. Despite operating since 1985, the Kenyir Reservoir’s total GHG emissions remain high compared to other global reservoirs, likely due to its tropical location and high organic carbon content. Elevated GHG emissions were recorded along the Terengganu River, near the dam discharge outlets, with gradual reductions observed downstream. Despite the estuary’s smaller surface area, more GHGs are emitted there than in the river. Overall, the Terengganu River catchment emits approximately 572 Gg CO2-equivalent annually, with the Kenyir Reservoir accounting for the majority (94%). The river and the estuary contribute 0.5% and 5.5%, respectively. This study highlights the substantial role of tropical hydropower reservoirs and their downstream river networks in the global GHG budget, emphasizing the need for further investigation into the factors influencing GHG dynamics in tropical river systems.
Keywords: Greenhouse gas emissions; Hydropower dam; Tropical reservoir; River damming; Tropical river